KINERJA GURU BAHASA INDONESIA DI SMK - Syuraiani Syuraiani Syuraiani (UNIVERSITAS BENGKULU, 2016)
The objective of the research is to describe: how the Indonesian languange teachers understand the curriculum, performance in arranging of syllabus, perform in arranging lesson planning, perform in teaching and learning process, performance to evaluate execution. The method of the research was descriptive qualitative . This Research was conducted by four Indonesian languange teachers in SMKN I Ketahun. The collecting data were observation, interview, and document. The results show that Indonesian languange teachers in still require training and practices to increase professionality in their performance as teachers, good understanding about curriculum, compilation of RPP, good method and good teaching media and also suitable assessment.Keywords: performance teachers, learning, competence.